MENYOAL PENYIMPANGAN PRINSIP SYARI’AH PADA LEMBAGA KEUANGAN SYARI’AH - Syahril, Syahril; Moh. Baqir Ainun; Mohammad Herli (Journal of Innovation Research and Knowledge, 2025)
BPRS Bhakti Sumekar is a sharia financial institution achievers, but the sharia financial institution achievers don’t guarantee of full implementation of sharia principles. Some costemers of pembiayaan modal kerja say sharia financial institution practices isn’t much different from conventional practices. And the customers say he doesn’t know for sure the reason of the object do like that. This efent will lead to negative perceptions of the community without knowing the factors causing deviations on the principles of sharia.This research focus is tabungan barokah products because it’s the most sought product on saving’s customers. In addition, research is also done of deposito mudharabah products because it’s the largest source of funding in the object. Researchers also examine of pembiayaan modal kerja products with mudharabah contract because target of this products to UMKM according with the vission and mission of BPRS Bhakti Sumekar Sumenep to empower UMKM in Sumenep. The purpose of this study is (1) to knowing the implementation of sharia principles on BPRS Bhakti Sumekar Sumenep, and (2) to knowing the factors causing deviations on the principles of sharia on BPRS Bhakti Sumekar Sumenep. The research method used is qualitative with comparative approach. The author will collect data by observation, interview and documentation. Then the author will compare the data obtained with SAK Syari'ah and Fatwa DSN MUI. If the result of comparison is deviations on the principles of sharia, the author will investigate the factors causing deviations on the principles of sharia.The results from this research is show deviations on the principles of sharia in tabungan barokah products, deposito mudharabah products, and pembiayaan modal kerja product with mudharabah contract. The factors causing deviations on the principles of sharia on the object is competition between financial institutions, and factors to avoid losses and ensure the profit to be earned BPRS Bhakti Sumekar Sumenep.